Comparison of polyethylene glycol vs sodium picosulphate vs sodium biphosphonate by efficacy in bowel cleansing and patients' tolerability: a randomised trial. (August 2016) - Heetun, Z.; Crowley, R.; Zeb, F.; Kearns, D.; Brennan, M.; O'Connor, C.; Courtney, G.; Aftab, A.
Abstract Introduction Adequate bowel preparation is necessary for a complete colonoscopy. Polyethylene glycol-electrolyte oral solution (PEG-EOS), sodium picosulphate (SS) and sodium biphosphonate (SP) are the three most commonly used purgative agents. We aimed to determine their efficacy and tolerability compared to each other in a randomised study. Methods 313 patients were randomly assigned to receive either PEG-EOS, SS or SP. Patients completed a tolerability score pre-colonoscopy. A cleanliness score was used to document adequacy of bowel preparation. A separate group of patients completed taste scores for the three cathartic agents before and after addition of flavour. Results PEG-EOS was the worst-tolerated regimen but achieved the highest rates of right colonic cleansing and the lowest rate of incomplete colonoscopies. There were no statistical differences in the rates of rectosigmoid and mid-gut cleansing among the three agents. SS was by far the preferred purgative in the taste assessment study. Addition of flavour increased significantly taste scores for PEG-EOS. Conclusion For adequate bowel cleansing PEG-EOS is the most effective but is the least tolerated and least preferred among patients. Addition of flavour increases significantly patients' acceptance of PEG-EOS.